ANALISA LAJU KOROSI PADA PIPA CARBON STEEL A.106. GR.B PADA PROSES PRODUKSI MINYAK BUMI DI LEPAS PANTAI - Meryanalinda; Agus Umartono; Mustafa Sihombing (Wahana Teknik, 2022)
In the production process of oil and gas, corrosion is one of the factors to considered in planning the pipe will be used to adjust to the needs of operation. In this study, the pipe material used in the oil and gas production process is A.106. GR.B. To prevent potential failure or damage during operation, the corrosion rate is monitored using the weight loss method with a coupon sample and also measuring the pipe wall thickness with Ultrasonic Thickness Measurement (UTM). The pipes taken as data are 4 production well pipes, namely Well Z2, Well Z3, Well Z4 and Well Z5. The results of data processing showed that the corrosion rate value on ell Z5 is 3.20 mpy, Z3 is 1.95 mpy, Z4 is 1.82 mpy and Z2 is 0.92 mpy. While the corrosion rate values obtained through calculation with pipe wall thickness measurements are well Z5 which 4.01 mpy, Z3 is 3.24 mpy, Z4 is 3.20 mpy and Z2 is 1.50 mpy. Base on the assessment of the corrosion rate with the two methods above, the key is that the corrosion rate by measuring the thickness of the pipe wall has a greater value due to external corrosion the occurs in the well pipe of the production process. From the results of the corrosion rate value obtained, well pipes that have greater corrosion value will have a shorter remaining pipe life.